Echocardiographic Wall Motion Score in the Naive Patients of Non-ST Segment Elevation Acute Coronary Syndrome Regarding their Early Mortality - Aijaz Ahmed Memon, Ghulam Fareed Shah, Shahid Hussain Memon, Gul Hassan Brohi, Anwar Ali Shaikh, Ambreen Haidar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To evaluate the association of echocardiographic wall motion score (WMS) with early mortality (30-days) among patients with non-ST-Segment Elevation Acute Coronary Syndrome (NSTE-ACS). Material and methods: This descriptive case series study was conducted at the cardiology department at LUMHS from October 2015 to March 2016. Patients with NSTE-ACS and positive cardiac biomarkers, patients older than 25 years, and both genders admitted to CCU were included. Standard indoor treatment was done in these patients. Evaluation of wall motion score was done by echocardiography by 2D echo. All patients were monitored for early cardiac event-related mortality (30 days). The self-made Performa logged all of the information gathered. SPSS version 26.0 was used to analyze all of the data. Results: In this study, a total of 148 cases of NSTE-ACS were studied. Most of the patients were aged more than 40 years, and males were in the majority 93(62.8%). Reginal wall motion was in 105(70.9%) of the cases. In 88(59.5%) of the cases, the ejection fraction was <40% and in 58(40.5%) of the cases it was >40%. CKMB was raised in 69(46.6%) of the cases, and troponin T was positive in all of the cases. The overall short-term mortality rate was 20.3%, which was significantly associated with a high grade of wall motion score (p-0.001). Conclusions: It was concluded that echocardiographic wall motion score was correlated significantly to short-term mortality (30-day) among new patients presented with NSTE-ACS. Keywords: Acute coronary syndrome, WMS, NSTE, early mortality